Existence results for a class of quasilinear Schrödinger equations with singular or vanishing potentials. (July 2022) - Badiale, Marino; Guida, Michela; Rolando, Sergio
Abstract: Given two continuous functions V r ≥ 0 and K r > 0 ( r > 0 ), which may be singular or vanishing at zero as well as at infinity, we study the quasilinear elliptic equation − Δ w + V | x | w − w Δ w 2 = K ( | x | ) g ( w ) in R N, where N ≥ 3 . To study this problem we apply a change of variables w = f ( u ), already used by several authors, and find existence results for nonnegative solutions by the application of variational methods. The main features of our results are that they do not require any compatibility between how the potentials V and K behave at the origin and at infinity, and that they essentially rely on power type estimates of the relative growth of V and K, not of the potentials separately. Our solutions satisfy a weak formulations of the above equation, but we are able to prove that they are in fact classical solutions in R N ∖ 0 . To apply variational methods, we have to study the compactness of the embedding of a suitable function space into the sum of Lebesgue spaces L K q 1 + L K q 2, and thus into L K q ( = L K q + L K q ) as a particular case. The nonlinearity g has a double-power behavior, whose standard example is g ( t ) = min t q 1 − 1, t q 2 − 1 , recovering the usual case of a single-power behavior when q 1 = q 2 .